Selenium-Enriched Pollen Grains of Olea europaea L.: Ca2+ Signaling and Germination Under Oxidative Stress - Del Pino, Alberto Marco; Regni, Luca; D’Amato, Roberto; Tedeschini, Emma; Businelli, Daniela; Proietti, Primo; Palmerini, Carlo Alberto (Frontiers in Plant Science, 2019)
Selenium (Se) shows antioxidant properties that can be exploited in plants to combat abiotic stresses caused by reactive oxygen species produced in excess (ROS). Here, we show that the Se-fertilisation of olive trees with sodium selenate effectively protects the pollen from oxidative stress. Pollen isolated from plants treated with Se or from untreated controls was incubated in vitro with H2O2 to produce an oxidative challenge. Given the impact of ROS on Ca2+ homeostasis and Ca2+-dependent signalling, cytosolic Ca2+ was measured to monitor cellular perturbations. We found that H2O2 interrupted Ca2+ homeostasis only in untreated pollen, while in samples treated in vitro with sodium selenate or selenium methionine, Ca2+ homeostasis was preserved. Furthermore, germination rates were considerably better maintained in Se-fertilised pollen compared to non-fertilised pollen (30% vs. 15%, respectively) after exposure to 1 mM H2O2. The same was observed with pollen treated in vitro with Se-methionine, which is the organic form of Se, in which part of the fertigated sodium selenate is converted in the plant. Combined, our results show a close correlation between ROS, Ca2+ homeostasis and pollen fertility and provide clear evidence that Se-fertilisation is a potential approach to preserve or improve agricultural productivity.